Tinjauan Terhadap Peraturan Digital Economy Dan Hukum Pajak Dalam Undang-Undang Pajak Pertambahan Nilai - Bella Andika Putri (UIN JAKARTA, 2019)
AbstractThe philosophy of Value-Added Tax (VAT) is a tax on consumption which is severely influenced by the development of business transaction and consumption pattern of society. In order to be the tool of social engineering and give legality of justice, Law Number 42 of 2009 should give certainty of law related to VAT imposition on transaction influenced intensely by business model growing in line with social development. Information technology development endorses the digital economy. Despite the fast growth of the digital economy in Indonesia, in line with the consistent growth of public and government consumption, the VAT revenue does not grow for consecutive three years. Law Number 42of 2009 does not prescribe explicit imposition VAT. Provision of VAT imposition on the digital economy makes VAT Law does not give justice legality and does not function as a tool of social engineering.Keywords: Value-Added Tax (VAT), Digital Economy, Justice Legality.